(untitled) (مجلة الواحات للبحوث والدراسات, 2022)
ملخص: تضطلع البلديات بالعديد من المهام المتعلقة بالخدمات العمومية الأساسية وكذا المرتبطة بالمشاريع التنموية، وتستخدم في سبيل تجسيدها مجموعة من الموارد المالية الذاتية وأيضا الناتجة من المساعدات المالية المركزية، وانطلاقا من هذه النقطة الأخيرة، نحاول من خلال هذه الورقة البحثية تسليط الضوء على ضرورة ربط الإعانات المقدمة للبلديات بنتائج التحليل المالي لضمان تحميل المسؤولين المحليين مسؤولية تحسين الأداء. اعتمادنا على وصف منهجية عمل برنامج التنمية الحضرية والحوكمة المحلية التونسي، ومن خلال جمع مختلف المعطيات المتعلقة بالبرنامج توصلنا إلى أن طريقة إسناد المساعدات ترتبط بمجموعة من الشروط الواجب تحقيقها بخصوص ثلاثة مجالات للأداء المحلي، وتبعث بذلك على نشر روح العمل وتدعيم ‎المسؤولية في تحسين الأداء المحلي للبلديات. ‏‎ ‎ الكلمات المفتاحية: الإعانات المركزية؛ البلديات؛ التنمية المحلية؛ الأداء المالي؛ الميزانية المحلية. Abstract: Municipalities carry out many tasks related to basic public services as well as development projects, and using their own resources but also central financial aid, and from this last point, we try to stress the need to link subsidies to municipalities with the results of the financial analysis to ensure that local officials are held accountable for improving performance. Based on the description of the methodology of the Tunisian Urban Development and Local Governance Programme, and collecting various data on the programme, we concluded that the aid method is linked to a set of conditions to be met in three areas of local performance, thus spreading the spirit of work and strengthening responsibility in improving the local performance of municipalities. Key words: Central subsidies; municipalities; local development; financial performance; local budget.